1977
DOI: 10.1093/ajcn/30.10.1623
|View full text |Cite
|
Sign up to set email alerts
|

Are Eskimos more or less obese than other Canadians? A comparison of skinfold thickness and ponderal index in Canadian Eskimos

Abstract: Skinfold thickness, height, and weight measurements were recorded from 1964 through 1970 for more than 1,000 adult Eskimos who resided in the Central and Eastern Canadian Arctic. Among the men and women of all age groups, 70 to 83% had a low ponderal index (PI less than 12.5). Nutrition Canada reported similar rates in 200 adult Eskimos and therefore considered Eskimos, especially Eskimo men, as more obese than other Canadians. Thin skinfolds were found in most Eskimo men, including those with a low PI. The us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Among Canadian Eskimos, a truncal fat distribution (ratio of tricepsasubscapular suprailiac skinfolds) was greater in women than men. 26 The results are also somewhat consistent with the data presented by Johnston et al 27 for urban Native American school children, which indicated that Native American females, but not males, tend to carry proportionally more subcutaneous fat on the trunk, relative to reference data.…”
Section: Discussionsupporting
confidence: 88%
“…Among Canadian Eskimos, a truncal fat distribution (ratio of tricepsasubscapular suprailiac skinfolds) was greater in women than men. 26 The results are also somewhat consistent with the data presented by Johnston et al 27 for urban Native American school children, which indicated that Native American females, but not males, tend to carry proportionally more subcutaneous fat on the trunk, relative to reference data.…”
Section: Discussionsupporting
confidence: 88%
“…Calls for an Inuit-specific growth reference (3) largely rest on the pattern of low height-forweight due to high sitting-to-standing height ratios observed in past studies of Inuit populations (6)(7)(8)16). However in a longitudinal study of Greenland Inuit children, BeckerChristensen reports that stature remains consistent with Danish reference values until the age of 14 years in boys and 11 years in girls, when decreased standing height gives rise to a higher sitting height ratio compared to Danish children (22).…”
Section: Resultsmentioning
confidence: 99%
“…Schaeffer (239) fo und that the Eskimos's mean skinfold thickness was 5.8-6.5 mm, compared to 15. 1-17.2 mm fo r young non-Eskimo adults in Toronto.…”
Section: Hypothesis 2: Mechanical Support and Protection For Organsmentioning
confidence: 95%